Impact of vitamin D on cognitive functions in healthy individuals: A systematic review in randomized controlled clinical trials - Silva, Ana Beatriz Januário da; Barros, Waleska Maria Almeida; Silva, Mayara Luclécia da; Silva, José Maurício Lucas; Souza, Ana Patrícia da Silva; Silva, Karollainy Gomes da; de Sousa Fernandes, Matheus Santos; Carneiro, Antonietta Cláudia Barbosa da Fonseca; Toscano, Ana Elisa; Lagranha, Cláudia Jacques (Frontiers in Psychology, 2022)
Cognition is understood as aspects related to knowledge, learning, and understanding, as well as the ability to develop these functions. Vitamins and minerals influence the functioning of several functions in the central nervous system and can help maintain brain health and cognitive function throughout life. In this review, we gathered and analysed randomized clinical trials carried out in healthy adults, which does not concern intellectual and/or mental processes that involve cognitive functions and their influence by serum levels of vitamin D (vit D). To do so, we adopted the PRISMA method criteria and registered it in the PROSPERO database. The search was performed in PubMed (MEDLINE), PsycINFO, Science Direct, Scopus, and Web of Science databases. The 5 most frequent cognitive domains in the selected studies were transmitted: processing speed, attention, verbal learning/memory, executive function, and general cognitive functions. We found that there is positive changes in the following domains: verbal memory and verbal working memory, learning memory, attention, executive function, and also cognitive function in general. Geographical aspects, age group, methods, and tools used to analyse the relationship between cognitive function and cognitive function were also discussed. We highlight the following suggestions for improvements that vitamin D supplementation may promote in the cognitive domains of the in healthy adults: a) low doses between 400 IU/d and 600 IU/d seem to be more effective when compared to doses between 2400 IU/d and 5000 IU/d; b) food fortification and enrichment with vit D, need further studies, as they seem to be more or as effective as synthetic supplementation; c) more clinical trials with young adults are needed, in order to understand positive changes promoted by supplementation with this vitamin in cognitive functions.